Hexavalent Chromium Removal from Industrial Wastewater by Adsorption and Reduction onto Cationic Cellulose Nanocrystals - Francisco de Borja Ojembarrena; Hassan Sammaraie; Cristina Campano; Angeles Blanco; Noemi Merayo; Carlos Negro (Nanomaterials, 2022)
Cationic cellulose nanocrystals (CCNC) are lignocellulosic bio-nanomaterials that present large, specific areas rich with active surface cationic groups. This study shows the adsorption removal of hexavalent chromium (Cr(VI)) from industrial wastewaters by the CCNC. The CCNC were synthetized through periodate oxidation and Girard’s reagent-T cationization. The high value of CCNCs cationic groups and anionic demand reveal probable nanocrystal-Cr(VI) attraction. Adsorption was performed with synthetic Cr(VI) water at different pH, dosage, Cr(VI) concentration and temperature. Fast removal of Cr(VI) was found while operating at pH 3 and 100 mg·L−1 of dosage. Nevertheless, a first slower complete removal of chromium was achieved by a lower CCNC dosage (40 mg·L−1). Cr(VI) was fully converted by CCNC into less-toxic trivalent species, kept mainly attached to the material surface. The maximum adsorption capacity was 44 mg·g−1. Two mechanisms were found for low chromium concentrations (Pseudo-first and pseudo-second kinetic models and continuous growth multi-step intraparticle) and for high concentrations (Elovich model and sequential fast growth-plateau-slow growth intraparticle steps). The Sips model was the best-fitting isotherm. Isotherm thermodynamic analysis indicated a dominant physical sorption. The Arrhenius equation revealed an activation energy between physical and chemical adsorption. CCNC application at selected conditions in industrial wastewater achieved a legal discharge limit of 40 min.